Land-use dynamics in the Sahelian zone in eastern Niger–monitoring change in cultivation strategies in drought prone areas - Reenberg, Anette (Journal of Arid Environments, 1994)
Landscape dynamics is important in the holistic analysis of environmental degradation in semi-arid regions. Large variations in time and space affecting key parameters, especially precipitation, call for dynamic analytical methods with the emphasis on monitoring change. Based on one example from eastern Niger (Goudoumaria) it is demonstrated how high-resolution satellite images, Landsat TM, can provide information on land use. The study reveals important changes in the relationship between land use and landscape with regard to new cultivation on soils more vulnerable to erosion.
openalex: W2032861420 mag: 2032861420
Keywords: openalex:import